1990
DOI: 10.1111/j.1699-0463.1990.tb01062.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinically undiagnosed malignant tumours found at autopsy

Abstract: In a series of over 20,000 autopsies carried out over a 25‐year period, 700 cancers (11%) were found in patients in whom the diagnosis of cancer had not been considered relevant clinically. In over half of them the unrecognized tumour was considered an incidential finding and thus of no importance to the individual concerned, though of epidemiological concern. As expected from the literature the main organs involved were kidney and prostate, with stomach cancer in third place. In contrast, the unrecognized can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…A recent study in the Czech Republic, another Central European country, found a 44% higher incidence of lung cancer in autopsy reports compared to clinical settings (17). Previous publications also reported a 11–28% higher incidence of cancer in autopsy reports than those reported by clinicians (18, 19). Based on a WHO report, Hungary is one of the countries with the highest autopsy rates for hospital deaths: dissection is performed in 36.9% of patients who die at hospitals (20).…”
Section: Discussionmentioning
confidence: 59%
“…A recent study in the Czech Republic, another Central European country, found a 44% higher incidence of lung cancer in autopsy reports compared to clinical settings (17). Previous publications also reported a 11–28% higher incidence of cancer in autopsy reports than those reported by clinicians (18, 19). Based on a WHO report, Hungary is one of the countries with the highest autopsy rates for hospital deaths: dissection is performed in 36.9% of patients who die at hospitals (20).…”
Section: Discussionmentioning
confidence: 59%
“…Prevalence estimates vary widely based on methods used and on age and other demographic factors in populations studied. 10 Extrapolations from autopsy series suggest that roughly 7–11% of those aged 50–75 harbor an internal malignancy, 11 13 and that cancer may be the unsuspected cause of death in 3–5%. 11 , 12 …”
Section: Universal Cancer Screening: Re-imagining the Paradigmmentioning
confidence: 99%
“…Diagnostic errors in medicine are on the rise and the incidence of post-mortem findings of undiagnosed malignancy at autopsy have been reported as high as 11% [ 1 ]. B cell lymphoma constitutes 80–85% of cases of Non Hodgkin’s lymphoma (NHL) in the Untied States, most of which are diffuse large B cell lymphomas (DLBCL, 32%), and is the seventh leading cancer in both male and female patients [ 2 ].…”
Section: Introductionmentioning
confidence: 99%